Rapid and widespread white matter plasticity during an intensive reading intervention - Elizabeth Huber; Patrick M. Donnelly; Ariel Rokem; Jason D. Yeatman (Nature Communications, 2018)
White matter properties correlate with cognitive performance in a number of domains. Here the authors show that altering a child’s educational environment though a targeted intervention program induces rapid, large-scale changes in the white matter, and that these changes track the learning process.